Self-association of [PtII(1,10-Phenanthroline)(N-pyrrolidyl-N-(2,2-dimethyl-propanoyl)thiourea)]+ and non-covalent outer-sphere complex formation with fluoranthene through cation-π interactions : a high resolution 1H and DOSY NMR study - Kotze, Izak Aldert (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2009.